The Correlation between 3M+ Behavior and The Incidence of Dengue Hemorrhagic Fever in Kupang City - Zaquelino Da Costa Moreira; Agus Setyobudi; Helga Jillvera Nathalia Ndun (Universitas Nusa Cendana, 2020)
Indonesia is a dengue-endemic area. DHF in Kupang City in 2014 was 487 cases, in 2015 was 665 cases, in 2016 was 1.213 cases, it was 2019 387 cases. The 3M+ behavior includes the habit of draining water storage, closing the water storage, burying old stuff, sowing larvicide powder, using mosquito insecticide, using mosquito bed-net, and avoiding the habit of hanging clothes. This study aims to analyze the relationship between 3M+ behavior and the incidence of DHF. This study was conducted in September 2019. This is a descriptive-analytic study with a case-control design. The results show variables related to the incidence of DHF are the behavior of draining water storage (P-value = 0.006), the behavior of closing the water storage (P-value = 0.002), and the behavior of using anti-mosquito insecticide (P-value = 0,000). Whereas the variables not related to the incidence of DHF are the behavior of burying old stuff (P-value = 0.616), the behavior of sowing larvicide powder (P-value = 0.493), the behavior of using mosquito nets (P-value = 0.067), and the behavior of hanging clothes (p-value = 0.512). It is recommended that 3M+ behavior should be done to prevent dengue hemorrhagic fever.